The Association of Peer Smoking Behavior and Social Support with Quit Success in Employees Who Participated in a Smoking Cessation Intervention at the Workplace - van den Brand, Floor A.; Nagtzaam, Puck; Nagelhout, Gera E.; Winkens, Bjorn; van Schayck, Constant P. (International journal of environmental research and public health, 2019)
The current study investigated whether quit success among employees who participated in a smoking cessation intervention at the workplace was associated with social support from, and the smoking behavior of, people in their environment. Tobacco-smoking employees (n = 604) from 61 companies participated in a workplace group smoking cessation program. Participants completed questionnaires assessing social support from, and the smoking behavior of, people in their social environment. They were also tested for biochemically validated continuous abstinence directly after finishing the training and after 12 months. The data were analyzed using mixed-effects logistic regression analyses. Social support from colleagues was positively associated with 12-month quit success (odds ratio (OR) = 1.85, 95% confidence interval (CI) = 1.14–3.00, p = 0.013). Support from a partner was positively associated with short-term quit success (OR = 2.01, 95% CI = 1.23–3.30, p = 0.006). Having a higher proportion of smokers in the social environment was negatively associated with long-term abstinence (OR = 0.81, 95% CI = 0.71–0.92, p = 0.002). Compared to having a non-smoking partner, long-term quit success was negatively associated with having no partner (OR = 0.48, 95% CI = 0.26–0.88, p < 0.019), with having a partner who smokes (OR = 0.40, 95% CI = 0.24–0.66, p < 0.001), and with having a partner who used to smoke (OR = 0.47, 95% CI = 0.26–0.86, p = 0.014). In conclusion, people in a smoker’s social environment, particularly colleagues, were strongly associated with quit success. The workplace may, therefore, be a favorable setting for smoking cessation interventions.